Plasma amino acid profiles in young cross-country skiers - Mäki, M.; Jaakkola, M.; Kallio, T.; Karvonen, H.; Kilpeläinen, P.; Virtanen, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Exercise is accompanied by increased protein catabolism and changes in the plasma amino acid concentrations, as amino acids both influence on and reflect muscle protein synthesis and breakdown (van Loon 2014). For example, branched-chain amino acids leucine, isoleucine and valine affect protein synthesis in human skeletal muscles (Blomstrand et al. 2006) and ultra-endurance exercise causes muscle protein breakdown elevating plasma phenylalanine and tyrosine concentration (Borgenvik et al. 2012). In addition prolonged exercise and overtraining may decrease plasma glutamine concentration (Parry-Billings et al.1992).